Identification Of Muscle Sound (Mmg) In Human Body - Hmood, Khedher A. (1999)
From the biomedical engineering study on muscle fibers, there are two types of signals: Electromyography (EMG) signal and muscle sound (MMG). The EMG signal is generated by the human muscle and is detected by using stainless steel electrodes but the muscle sound MMG is detected using vibration detection sensor such as piezoelectric sensor. In this thesis, a suitable sensor has been used to detect the muscle sound in order to analyze its characteristics.